2006
DOI: 10.1111/j.1464-410x.2006.06211.x
|View full text |Cite
|
Sign up to set email alerts
|

Bothersome lower urinary tract symptoms 1 year after first delivery: prevalence and the effect of childbirth

Abstract: RESULTSOf the 344 women, 83 (24.2%) reported having a moderate to greatly bothersome frequency symptom at 36 weeks of gestation. After childbirth there was a statistically significant decline in the prevalence of bothersome frequency to 38 (9.6%) women ( P < 0.001).Bothersome SUI was present in 53 (15.4%) women at 36 weeks of gestation, and in 36 (10.5%) at 1 year after childbirth. Fifty-eight (16.9%) women reported having moderate to greatly bothersome urge UI (UUI) and at 1 year after childbirth, 51 (14.8%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
4
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 48 publications
10
64
4
8
Order By: Relevance
“…À luz dos conhecimentos atuais, a episiotomia constitui um tema de debate; embora a maioria dos estudos demonstre resultados semelhantes aos apresentados. [30][31][32] Em relação aos restantes fatores peri-parto, alguns autores também não demonstraram qualquer associação entre a IU pós-parto e a ocorrência de laceração perineal ou o peso do recém-nascido superior a 4000 gr. [31][32][33][34] Chamou-nos também a atenção o facto de que uma percentagem significativa das mulheres entrevistadas não recebeu qualquer tipo de orientação sobre a IU durante a gestação, e a maioria daquelas com IU no pós parto não procurou aconselhamento médico.…”
Section: Discussionunclassified
“…À luz dos conhecimentos atuais, a episiotomia constitui um tema de debate; embora a maioria dos estudos demonstre resultados semelhantes aos apresentados. [30][31][32] Em relação aos restantes fatores peri-parto, alguns autores também não demonstraram qualquer associação entre a IU pós-parto e a ocorrência de laceração perineal ou o peso do recém-nascido superior a 4000 gr. [31][32][33][34] Chamou-nos também a atenção o facto de que uma percentagem significativa das mulheres entrevistadas não recebeu qualquer tipo de orientação sobre a IU durante a gestação, e a maioria daquelas com IU no pós parto não procurou aconselhamento médico.…”
Section: Discussionunclassified
“…In studies of fecal incontinence (FI) and urinary incontinence (UI) during the postpartum period, UI is reported by 10-50% of women, [1][2][3][4][5][6] whereas FI is present in up to 25%. 2,3,7 The Pelvic Floor Disorders Network (PFDN) has previously published findings of the Childbirth and Pelvic Symptoms (CAPS) study, 8 which examined the prevalence of FI and UI in 3 cohorts of primiparous women.…”
Section: Abstract Childbirth; Fecal Incontinence; Quality Of Life; Urmentioning
confidence: 99%
“…9 Although several case series report the impact of postpartum UI on QOL, 3,4,6 data are very limited on the impact of FI on QOL in the postpartum period. In a Canadian study, 3 FI was present in 20.6% of 1305 primiparous women 6 months postpartum, and QOL varied significantly with the severity of both FI and UI.…”
mentioning
confidence: 99%
“…Proposed mechanisms include anatomic disruption, denervation to the pelvic floor, or trauma by vaginal delivery [1][2][3][4][5][6][7][8]. However, while these conditions have been shown to impact quality of life in the postpartum period [9][10][11][12], impact during pregnancy is less clear. Additionally, although previous reports have suggested that impaired body image may occur with prolapse [13], the effect of urinary and fecal incontinence on body image has not been previously documented.…”
Section: Introductionmentioning
confidence: 99%